Characterization of porcine intestinal receptors for the K88ac fimbrial adhesin of Escherichia coli as mucin-type sialoglycoproteins. - Erickson, A K (1994)
We have previously identified two K88ac adhesion receptors (210 and 240 kDa) which are present in membrane preparations from adhesive but not nonadhesive porcine intestinal brush border cells; these adhesin receptors are postulated to be important determinants of the susceptibility of pigs to K88ac+ enterotoxigenic Escherichia coli infections (A.K. Erickson, J.A. Willgohs, S.Y. McFarland, D.A. Benfield, and D.F. Francis, Infect. Immun. 60:983-988, 1992). We now describe a procedure for the purification of these two receptors. Receptors were solubilized from adhesive intestinal brush border vesicles using deoxycholate and were purified by gel filtration chromatography on Sepharose CL-4B and then by hydroxyapatite chromatography. Amino acid compositional analyses indicated that the two receptors have similar amino acid compositions. The most distinguishing characteristic of both receptors is a high percentage of threonine and proline residues. Neuraminidase treatment caused the K88ac adhesin receptors to migrate with a slower mobility on sodium dodecyl sulfate-polyacrylamide gel electrophoresis gels, indicating that these receptors are sialoglycoproteins. Results from lectin-binding studies indicated that the receptors contain O-linked oligosaccharides composed of galactosyl (beta-1,3)N-acetylgalactosamine, alpha-linked fucose, galactosyl(beta-1,4)N-acetylglucosamine, sialic acid, galactose, and N-acetylgalactosamine. Collectively, these characteristics indicate that the K88ac adhesin receptors are mucin-type sialoglycoproteins.